Ranging behaviour of long-tailed macaque (macaca fascicularis) at Taman PD Utama, Port Dickson, Negeri Sembilan, Peninsular Malaysia - Nur Anis Suraya Ramli (2024)
This study reports on the ranging behaviour of a group of long-tailed macaques (Macaca fascicularis) in Taman Pd Utama, Port Dickson, Negeri Sembilan. Data on ranging behaviour were collected daily for 20 days and were performed 6 days a week. Observations focused on distance movement and canopy level use by groups of long-tailed macaques. They often travel between 100 and 400 m per day. They use areas close to human settlements because of the high availability of food. The results of the study found that the long-tailed macaques do not seem to move far from their residential area. The forest canopy layer most frequently used by the research group is ground level (32.94%), followed by lower layer canopy (28.34%), middle canopy (20.71%), upper canopy (14.40%), and the lowest is the emergence (3.62%). Overall, the ranging behavior of the study group is influenced by food distribution and is also influenced by other factors. Therefore, this study shows the importance of understanding the canopy level used and the movement distance used by long-tailed macaques.